Removing the veil of ignorance in assessing the distributional impacts of social policies - Pedro Carneiro; Karsten T Hansen; James J Heckman (Institute for Labour Market Policy Evaluation (IFAU), 2002)
This paper summarizes our recent research on evaluating the distributional consequences of social programs. This research advances the economic policy evaluation literature beyond estimating assorted mean impacts to estimate distributions of outcomes generated by different policies and determine how those policies shift persons across the distributions of potential outcomes produced by them. Our approach enables analysts to evaluate the distributional effects of social programs without invoking the Veil of Ignorance assumption often used in the literature in applied welfare economics. Our methods determine which persons are affected by a given policy, where they come from in the ex-ante outcome distribution and what their gains are. We apply our methods to analyze two proposed policy reforms in American education. These reforms benefit the middle class and not the poor.
Keywords: I28; 330; social programs; welfare economics